Avaliação das condições de acessibilidade com necessidades especiais em cinco escolas municipais da cidade de Abaetetuba – PA - SARGES, Diana Helena Sousa (2024)
As the school is one of the most frequented places by the individuals of a society, there is a need to find out how school buildings are becoming adapting to this new law. If the watchword currently is to promote a egalitarian education, in the sense of presenting students with all means of access, school buildings urgently need to adapt to the rules accessibility aspects of the Brazilian Standard (NBR) 9050 of 2004. The objective of this research was to verify the current conditions of accessibility of some schools in the municipality of Abaetetuba and the existence of adaptation projects regulators, according to NBR 9050/2004. The present study was carried out in five elementary schools in the city of Abaetetuba and was characterized as a field research, using observation as a technique directly, through a guiding protocol of this NBR that exposes the conditions of accessibility. The results found for each of the items investigated show that the school units are far from the ideal model of care for people with special needs, being short of offering a good quality physical structure, a fact that excludes people with special needs within the school environment in the municipality of Abaetetuba.